Pengaruh Persepsi Nilai Dan Kepuasan Konsumen Terhadap Keputusan Pembelian Ulang Pada Cafe Beeginning - Lalu Izam Hikmawan; Ismunandar Ismunandar (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
In the city of Bima itself, more precisely in Raba Dompu, Rasa Nae Barat subdistrict, modern market growth has increased very rapidly and competition is very rapid, especially for cafes that have similar products. The increasing number of competitors means that customers have many choices to get products that meet their expectations so that as a result of this condition consumers are more careful and smart when dealing with the products being launched. This is also felt by the starting cafe in the city of Bima, which continues to innovate day by day the products it offers to consumers. Perceived value is one of the factors to support the company to run smoothly, not only that, consumer satisfaction also influences the consumer's repurchase decision, the superiority of the product is known to consumers and can make consumers interested in trying it and then getting satisfaction from it. that product.